A Constructivist Institutionalism Perspective of Disaster and Crisis Countermeasure in Indonesia - Darmastuti, Ari (Forum Geografi, 2020)
As a country that lies in the area known as the Ring of Fire, Indonesia is prone to many disasters and the aftermaths of such crises, from low-scale earthquake events up to mega-magnitude tsunami, earthquakes and volcanoes. The current Covid-19 pandemic is another disaster in mega magnitude scale that the country must deal with.  Research on disaster risk reduction and management has been conducted, yet little is known about how governments, as the most important actor in disaster countermeasures, develop their institutions based on unpredictable exogenous factors.  This study aims to critically analyse disaster and crisis countermeasures in Indonesia based on a constructivist perspective.  The data for this qualitative study were mainly collected through document studies, together with some interviews.  The mega-crisis due to the Covid-19 pandemic has resulted in the establishment of long-term national, provincial, local, and lower level task forces all over Indonesia.  This kind of institutional arrangement has never previously been developed in the country, not even after the 2006 mega-tsunami which hit various provinces and led to a huge death toll of over 100,000. The study shows that although the institutional arrangements for disaster countermeasures in Indonesia are based on the same law, the implementation of institutional structures and practices as disaster countermeasures vary greatly.